Lifestyle Risk Factors and Cognitive Outcomes from the Multidomain Dementia Risk Reduction Randomized Controlled Trial, Body Brain Life for Cognitive Decline (BBL‐CD). Issue 11 (9th September 2020) - McMaster, Mitchell; Kim, Sarang; Clare, Linda; Torres, Susan J.; Cherbuin, Nicolas; DʼEste, Catherine; Anstey, Kaarin J.
Abstract : BACKGROUND/OBJECTIVES: To evaluate the efficacy of a multidomain intervention to reduce lifestyle risk factors for Alzheimer's disease (AD) and improve cognition in individuals with subjective cognitive decline (SCD) or mild cognitive impairment (MCI). DESIGN: The study was an 8‐week two‐arm single‐blind proof‐of‐concept randomized controlled trial. SETTING: Community‐dwelling individuals living in Canberra, Australia, and surrounding areas. PARTICIPANTS: Participants were 119 individuals (intervention n = 57; control n = 62) experiencing SCD or MCI. INTERVENTION: The control condition involved four educational modules covering dementia and lifestyle risk factors, Mediterranean diet, physical activity, and cognitive engagement. Participants were instructed to implement this information into their own lifestyle. The intervention condition included the same educational modules and additional active components to assist with the implementation of this information into participants' lifestyles: dietitian sessions, an exercise physiologist session, and online brain training. MEASUREMENTS: Lifestyle risk factors for AD were assessed using the Australian National University‐Alzheimer's Disease Risk Index (ANU‐ADRI), and cognition was assessed using Alzheimer's Disease Assessment Scale‐Cognitive subscale, Pfeffer Functional Activities Questionnaire, Symbol Digit Modalities Test (SDMT), Trail Making Test‐B, and Category Fluency. RESULTS: The primary analysis showed that the intervention group had a significantly lower ANU‐ADRI score (χ 2 = 10.84; df = 3; P = .013) and a significantly higher cognition score (χ 2 = 7.28; df = 2; P = .026) than the control group. A secondary analysis demonstrated that the changes in lifestyle were driven by increases in protective lifestyle factors (χ 2 = 12.02; df = 3; P = .007), rather than a reduction in risk factors (χ 2 = 2.93; df = 3; P = .403), and cognitive changes were only apparent for the SDMT (χ 2 = 6.46; df = 2; P = .040). Results were robust to intention‐to‐treat analysis controlling for missing data. CONCLUSION: Results support the hypothesis that improvements in lifestyle risk factors for dementia can lead to improvements in cognition over a short time frame with a population experiencing cognitive decline. Outcomes from this trial support the conduct of a larger and longer trial with this participant group.